Análisis de tensiones en generadores de vapor para uso nuclear - Darnond, L.; Larumbe Valle, J. M.; López, Rául J. M. (Comisión Nacional de Energía Atómica; Argentina, 1974)
Fil: Darnond, L. Comisión Nacional de Energía Atómica; Argentina